Association Between Informal Employment and Positive COVID-19 Cases in Peru: Asociación entre el empleo informal y los casos positivos de COVID-19 en el Perú | 秘鲁非正式就业与COVID-19阳性病例之间的关联 - Pascual-Guevara, Milagros (2024)
Objectives: To identify the association between the number of informal workers and the number of positive COVID-19 cases in Peru. Methods: Data from the National Institute of Statistics and Informatics of Peru and the National COVID-19 Database were used. Bivariate and multivariate linear regression analyses were conducted to assess the relationship between the number of informal workers, population density, altitude, and the number of positive COVID-19 cases. Results: The bivariate analysis showed that the number of informal workers was significantly associated with positive cases in both high and low altitude regions (p<0.001). In the multivariate analysis, informal workers (p<0.001), population density (p=0.02), and altitude (p<0.001) were found to be associated with the number of positive COVID-19 cases. Conclusions: Informal workers are common in low- and middle-income countries where social security is lacking, and they depend economically on daily wages. Their situation worsened due to social mobility restrictions, which forced them to continue working and consequently increased their susceptibility to infection, further becoming a source of contagion.